Crystallization-induced microcellular foaming of poly (lactic acid) with high volume expansion ratio. (October 2017) - Chen, Peng; Wang, Wenbo; Wang, Yaqiao; Yu, Kesong; Zhou, Hongfu; Wang, Xiangdong; Mi, Jianguo
Abstract: Currently, the preparation of microcellular semi-crystalline polymer foam with a high volume expansion ratio (VER) using supercritical CO2 as blowing agent is a big challenge in the world. In this paper, a methodology for the preparation of microcellular poly (lactic acid) (PLA) foams with high VER by crystallization induction and chain extension modification was proposed. Phenylphosphonic acid zinc salt (PPZn) as a crystallization nucleating agent and multi-functional epoxy-based chain extender (CE) were introduced to enhance the crystallization property and the melt elasticity of PLA respectively. The effects of PPZn and CE on the crystallization properties and foaming propertiess of pure PLA, PLA/PPZn, PLA/CE, and PLA/CE/PPZn samples were investigated using differential scan calorimeter (DSC) and scanning electron microscope. The DSC results of four PLA samples showed that the addition of PPZn obviously improved the crystallinity and crystallization temperature of unfoamed PLA and PLA/CE samples. Then PLA foams were prepared using a high pressure vessel at difference isothermal saturating temperatures. The corresponding result showed that the high-melting temperature crystals formed by molecular chain rearranging in the isothermal saturating process were regulated and controlled through adjusting the saturating temperature. For PLA foam and PLA/PPZn foam, the addition of PPZn played an important role in increasing high-melting temperature crystals and improving cellular morphology of PLA sample at the same saturation temperatures; the cell density of PLA/PPZn foam was about 1.0 × 10 11  cells/cm 3 and the cell size of PLA/PPZn foam was around 1.9 μm at the saturation temperatures of 145 °C. For PLA/CE foam and PLA/CE/PPZn foam at the saturation temperatures of 145 °C, their VERs increased from 1.9 times to around 10.6 times compared with that of PLA/PPZn foam with the addition of CE due to the increase of melt elasticity; the corresponding cell densities were all over 9.5 × 10 10  cells/cm 3 and their cell sizes were about 4.5 μm.